Hubungan Antara Tingkat Pendidikan Ibu, Anemia Saat Kehamilan, Dan Berat Bayi Lahir Rendah Terhadap Kejadian Stunting Pada Balita Di Puskesmas Selaawi Tahun 2022 - Muhammad Bushido Abdullah; Hidayat Widjajanegara; Zulmansyah (UNISBA Press, 2023)
Abstract. Stunting is a condition of developmental and growth disorders in infants over 2 years old caused by chronic malnutrition which can result in children's height being too short for their age. The prevalence of stunting in Garut district reaches 35.2%. Stunting risk factors are divided into extrinsic factors and intrinsic factors. The purpose of this study was to determine the relationship between the education level of the mother, anemia during pregnancy, and low birth weight with the incidence of stunting in toddlers at the Selaawi Health Center in 2022. The subjects of this study were toddlers 2-5 years old who had a MCH cohort, with a sample size of 140 using this technique. probability sampling. The research methodology is analytic observational with a retrospective approach. Statistical test using Fisher's exact test. The results show that stunting toddlers come from mothers with higher education 24.3% and from mothers with low education 75.7%. Toddlers who are not stunted come from mothers with a high education level of 37.1% and come from mothers with a low education level of 62.9%. Stunted toddlers come from mothers with a history of anemia during pregnancy 7.1%, and toddlers who are not stunted come from mothers with a history of anemia during pregnancy 2.9%. Stunted toddlers are toddlers with a history of LBW 10% and toddlers who are not stunted are toddlers with a history of LBW 2.9%. Statistical test results showed p> 0.05 for each independent variable tested. In conclusion, there is no relationship between maternal education level, anemia during pregnancy, and LBW with the incidence of stunting in toddlers at the Selaawi Health Center. Abstrak. Stunting merupakan keadaan gangguan perkembangan dan pertumbuhan pada bayi di atas 2 tahun yang disebabkan oleh kurang gizi kronis sehingga dapat mengakibatkan tinggi anak terlalu pendek berdasarkan usianya. Prevalensi stunting di kabupaten Garut mencapai 35,2%. Faktor risiko stunting terbagi menjadi faktor ekstrinsik dan faktor intrinsik. Tujuan penelitian ini mengetahui hubungan antara tingkat pendidikan ibu, anemia saat kehamilan, dan berat bayi lahir rendah dengan kejadian stunting pada balita di Puskesmas Selaawi tahun 2022. Subjek dari penelitian ini balita 2-5 tahun yang memiliki kohort KIA, dengan besar sampel 140 dengan teknik pengambilan sampel probability sampling. Metodologi penelitian ini adalah observasional analitik dengan pendekatan retrospective. Uji statistik menggunakan Fisher’s exact test. Hasil menunjukkan bahwa balita stunting berasal dari ibu dengan pendidikan tinggi 24,3% dan dari ibu dengan pendidikan rendah 75,7%. Balita tidak stunting berasal dari ibu dengan tingkat pendidikan tinggi 37,1% dan berasal dari ibu dengan pendidikan rendah 62,9%. Balita stunting berasal dari ibu dengan riwayat anemia saat kehamilan 7,1%, dan balita tidak stunting berasal dari ibu dengan riwayat anemia saat kehamillan 2,9%. Balita stunting merupakan balita dengan riwayat BBLR 10% dan balita tidak stunting merupakan balita dengan riwayat BBLR 2,9%. Hasil uji statistik menunjukkan p > 0,05 untuk setiap variabel bebas yang diuji. Simpulan, tidak terdapat hubungan tingkat pendidikan ibu, anemia saat kehamilan, dan BBLR dengan kejadian stunting pada balita di Puskesmas Selaawi.